Evaluation of curcumin and copper acetate against Salmonella Typhimurium infection, intestinal permeability, and cecal microbiota composition in broiler chickens - Leyva-Diaz, Anaisa A. (J Anim Sci Biotechnol, 2021)
BACKGROUND: Interest in the use of natural feed additives as an alternative to antimicrobials in the poultry industry has increased in recent years because of the risk of bacterial resistance. One of the most studied groups are polyphenolic compounds, given their advantages over other types of additives and their easy potentiation of effects when complexes are formed with metal ions. Therefore, the objective of the present study was to evaluate the impact of dietary supplementation of copper acetate (CA), curcumin (CR), and their combination (CA-CR) against Salmonella Typhimurium colonization, intestinal permeability, and cecal microbiota composition in broiler chickens through a laboratory Salmonella infection model. S. Typhimurium recovery was determined on day 10 post-challenge by isolating Salmonella in homogenates of the right cecal tonsil (12 chickens per group) on Xylose Lysine Tergitol-4 (XLT-4) with novobiocin and nalidixic acid. Intestinal integrity was indirectly determined by the fluorometric measurement of fluorescein isothiocyanate dextran (FITC-d) in serum samples from blood obtained on d 10 post-S. Typhimurium challenge. Finally, microbiota analysis was performed using the content of the left caecal tonsil of 5 chickens per group by sequencing V4 region of 16S rRNA gene. RESULTS: The results showed that in two independent studies, all experimental treatments were able to significantly reduce the S. Typhimurium colonization in cecal tonsils (CT, P < 0.0001) compared to the positive control (PC) group. However, only CA-CR was the most effective treatment in reducing S. Typhimurium counts in both independent studies. Furthermore, the serum fluorescein isothiocyanate dextran (FITC-d) concentration in chickens treated with CR was significantly lower when compared to PC (P = 0.0084), which is related to a decrease in intestinal permeability and therefore intestinal integrity. The effect of dietary treatments in reducing Salmonella was further supported by the analysis of 16S rRNA gene sequences using Linear discriminant analysis effect size (LEfSe) since Salmonella was significantly enriched in PC group (LDA score > 2.0 and P < 0.05) compared to other groups. In addition, Coprobacillus, Eubacterium, and Clostridium were significantly higher in the PC group compared to other treatment groups. On the contrary, Fecalibacterium and Enterococcus in CR, unknown genus of Erysipelotrichaceae at CA-CR, and unknown genus of Lachnospiraceae at CA were significantly more abundant respectively. CONCLUSIONS: CR treatment was the most effective treatment to reduce S. Typhimurium intestinal colonization and maintain better intestinal homeostasis which might be achieved through modulation of cecal microbiota. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40104-021-00545-7.